Comparing digital libraries with virtual communities from the perspective of e-quality. Issue 1 (11th March 2014) - Yan, Yalan; Zha, Xianjin; Zhang, Jinchao; Hou, Xiaorong
Abstract : Purpose: – In this study, the authors use the term "e-quality" to refer to information quality, system quality and service quality. This study aims to focus on e-quality, exploring and comparing users' perceptions of digital libraries and virtual communities in the hope that the results of this study can help lead to better understanding of the exact nature of e-quality as perceived by users. Design/methodology/approach: – A large-scale survey was conducted for data collection. Data collected from 334 users of digital libraries and virtual communities were used for data analysis. Findings: – The study finds that users are likely to perceive a higher level of information quality, system quality and service quality of digital libraries than of virtual communities. Practical implications: – The authors suggest that librarians do not need to have concerns over the challenge brought by virtual communities, which indeed have an increasing impact on the way a lot of people seek and gather information. Instead, they should encourage their users to use both digital libraries and virtual communities. The authors believe that the usage of these two types of information sources by users can efficiently inform each other, thus facilitating the e-quality of both digital libraries and virtual communities to reach excellence. Originality/value: – Building on the information systems (IS) success model, this study explores and compares users' perceptions of digital libraries and virtual communities in terms of e-quality, which the authors think presents a new view for digital library research and practice alike.